Doktrin Sakramen: Menelaah Makna Dan Signifikansi Sakramen Baptisan Dan Perjamuan Kudus" - Ariance Lende; Aprianus Lendrik Moimau (Jurnal Magistra, 2024)
Reincarnation or reincarnation is not a foreign term for Christians. Nearly all churches encourage their congregation to experience rebirth or new birth. This research uses literature studies to explore several GBI sources containing Church doctrine, primary sources for John Calvin's theological ideas from his writings, as well as secondary sources from theologians who have studied this issue. The researcher's perspective and experience as a GBI member cannot be ignored when contributing to this research. The idea that the Church is the unified body of Christ is a very familiar idea among Christians. This idea suggests that just as Christians whose faith is one with Christ, each of them also has the right to be one with other believers. The unity of the Church is promised through the Apostles' Creed, one of the confessions of faith which reads, "I believe in the holy Church" and continues to be a reminder through the symbolic sacrament of Holy Communion for unity among the faithful. at the table with God. Lack of understanding and acceptance of the correct concept of Holy Communion will give rise to wrong attitudes in society in welcoming Holy Communion, so that it does not bring any blessings, but rather punishment for those involved. The promise of baptism as the first step in discipleship becomes less influential in the path of faith because forgotten. The church must lead God's people into a time of renewal of baptismal promises in the context of church services to maintain ongoing commitment as a community of followers of Christ. This research uses documentary research methods to analyze the biblical and theological significance of Jesus' baptism in Matthew 3:13-17. understanding or concept of the sacrament of baptism in the Catholic Church. Based on data obtained through research, there are two differences in understanding between the Huler Wair rite and the sacrament of baptism in the Catholic Church. There are also similarities and differences between the two, which encourage the author to be more active in writing this article and try to understand it well.